2010
DOI: 10.3109/13550281003685839
|View full text |Cite
|
Sign up to set email alerts
|

Association of autism with polyomavirus infection in postmortem brains

Abstract: Autism is a highly heritable behavioral disorder. Yet, two decades of genetic investigation have unveiled extremely few cases that can be solely explained on the basis of de novo mutations or cytogenetic abnormalities. Vertical viral transmission represents a nongenetic mechanism of disease compatible with high parent-to-offspring transmission and with low rates of disease-specific genetic abnormalities. Vertically transmitted viruses should be found more frequently in the affected tissues of autistic individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 43 publications
1
37
1
1
Order By: Relevance
“…Moreover, polyomavirus genome was detected in postmortem brain tissues from individuals with autism, indicating the presence of infection in the brain of these patients [239] . Although the molecular mechanisms by which viral infections contribute to the pathology of autism via PGE 2 signaling are still largely unknown and often inconclusive, the animal models provide some indirect evidence that altered immune responses due to infections might contribute to the development of autism.…”
Section: Involvement Of Immunological Factorsmentioning
confidence: 99%
“…Moreover, polyomavirus genome was detected in postmortem brain tissues from individuals with autism, indicating the presence of infection in the brain of these patients [239] . Although the molecular mechanisms by which viral infections contribute to the pathology of autism via PGE 2 signaling are still largely unknown and often inconclusive, the animal models provide some indirect evidence that altered immune responses due to infections might contribute to the development of autism.…”
Section: Involvement Of Immunological Factorsmentioning
confidence: 99%
“…Varying reports have also implicated measles and mumps (Deykin and MacMahon, 1979), cytomegalovirus (Libbey et al, 2005), polyomaviruses (Lintas et al, 2010), and influenza (Atladottir et al, 2012;Deykin and MacMahon, 1979;Shi et al, 2003;Zhang et al, 2010) in the incidence of ASD. Some studies suggest fever as a correlate (Atladottir et al, 2012), with this risk potentially tempered by anti-fever medications, such as Advil, Tylenol, or Nyquil (Zerbo et al, 2013).…”
Section: Congenital Infectionmentioning
confidence: 99%
“…Given the diversity of infections that show a connection to the spectrum of autism disorders (Boksa, 2010;Libbey et al, 2005), as well as evidence from MIA models that reaction to infection rather than infection itself may lead to autismrelated symptoms (Shi et al, 2003), a possible common etiology may be the influence of the immune system (Gottfried et al, 2015;Lintas et al, 2010;Zhang et al, 2010). Cytokines, small cell-signaling proteins that act as immunomodulatory and endocrine messengers, have been implicated throughout the process of CNS development (Boulanger, 2009;Jones and Thomsen, 2013).…”
Section: Cytokinesmentioning
confidence: 99%
“…In a study on the effects of polyomavirus infection on postmortem brains, the temporocortical regions of 15 adults with ASD and 13 without underwent DNA extraction (Lintas et al 2010). Polyomaviruses are small viruses that are typically acquired during childhood.…”
Section: Animal Analogues For Human Subjects With Asdmentioning
confidence: 99%
“…Through polymerase chain reaction (PCR) and DNA sequence analysis, it was observed that heightened combined levels of BKV, JCV, and SV40 were significantly more frequent (67 %) in postmortem brains of individuals having had ASD than in controls (23 %). The vertical viral transmission hypothesis is thought to be involved in this pathway, using a mechanism in which the virus camouflages itself from the body's detection as a genetic transmission mode (Lintas et al 2010). More research is needed to determine the relation of the vertical viral transmission hypothesis in vitro with the manifestation of polyomavirus infections in postmortem brains of autistic individuals.…”
Section: Animal Analogues For Human Subjects With Asdmentioning
confidence: 99%